2003
DOI: 10.5301/jbm.2008.1279
|View full text |Cite
|
Sign up to set email alerts
|

Medullary breast carcinoma: Prognostic implications of p53 expression

Abstract: Medullary breast carcinoma (MBC) is a rare pathological type of breast cancer. The rate of p53 protein accumulation is higher in MBC than in common invasive ductal carcinoma. Whether this particular feature of MBC influences the outcome after treatment is unknown. We retrospectively analyzed the characteristics, treatment and outcome of 71 patients with MBC treated between 1981 and 1996. The median age was 51 years (range 27-81) and the median clinical tumor size was 25 mm (range 0-70 mm). Breast-conserving tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The current study was the first one to use competing risk models (CIF and SH models) to analyze the prognostic value of clinical variables to the BCSS of MCB and IDC. Our results showed IDC had a worse BCSS than MCB, which was consistent with previous studies 4, [13][14][15] . Larger tumor size, a greater number of positive regional nodes and unmarried status were found to promote the progression of Continued both MCB and IDC.…”
Section: Discussionsupporting
confidence: 93%
“…The current study was the first one to use competing risk models (CIF and SH models) to analyze the prognostic value of clinical variables to the BCSS of MCB and IDC. Our results showed IDC had a worse BCSS than MCB, which was consistent with previous studies 4, [13][14][15] . Larger tumor size, a greater number of positive regional nodes and unmarried status were found to promote the progression of Continued both MCB and IDC.…”
Section: Discussionsupporting
confidence: 93%
“…The reported incidence of medullary carcinoma is < 5%. 6,7,8 The typical medullary breast carcinoma requires five criteria for diagnosis, these are: predominantly (>75%) syncytial growth pattern of tumour, moderate to marked diffuse mononuclear stromal infiltrate, absence of microglandular features and intraductal component, grade II-III nuclear pleomorphism and microscopically completely circumscribed tumour growth. 3,5,9 In the present study, we found both typical and atypical type of medullary breast carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its poorly differentiated morphology represented a diagnostic challenge. The mutated p53 and overexpression of HER-2/neu were evaluated in studies, showing that the majority of MC had a positive nuclear expression of p53 [6,7], while there was no immunostaining of HER-2/neu [8].…”
Section: Introductionmentioning
confidence: 99%